2002
DOI: 10.1016/s0921-4526(02)00994-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental probes of the molecular hydrogen–carbon nanotube interaction

Abstract: Electrical transport (resistance R and thermoelectric power S), Raman scattering, and hydrogen adsorption are used to study the interaction of hydrogen molecules with ropes of single-walled carbon nanotubes. The data are consistent with H 2 physisorption under the experimental conditions investigated (4 KoTo500 K; 0.1 atmoPo20 atm). The response of S; R to 1 atm hydrogen at 500 K is consistent with the introduction of a new scattering channel for electrons/holes in the metallic tubes. Raman scattering from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 16 publications
6
47
0
Order By: Relevance
“…3. This result is consistent with many experiments, which reported that SWNTs have a certain hydrogen storage capacity at low temperature, [13][14][15] but have very low hydrogen uptake capacity at room temperature. [8][9][10][11][12] For H 2 molecules adsorbed on defected SWNTs, the situation is very different.…”
Section: B Adsorption Energies and Electron Density Contours Around supporting
confidence: 93%
See 3 more Smart Citations
“…3. This result is consistent with many experiments, which reported that SWNTs have a certain hydrogen storage capacity at low temperature, [13][14][15] but have very low hydrogen uptake capacity at room temperature. [8][9][10][11][12] For H 2 molecules adsorbed on defected SWNTs, the situation is very different.…”
Section: B Adsorption Energies and Electron Density Contours Around supporting
confidence: 93%
“…2. The collision energy, 0.01 eV, is equivalent to the average translational kinetic energy of a particle system at a thermal equilibrium temperature of ϳ77 K. The high sticking coefficient in this case is consistent with the experimental results, [13][14][15][16] which showed that hydrogen uptake under cryogenic operating conditions were more favorable than at an ambient temperature. The second feature shown in Fig.…”
Section: A Hydrogen Molecules Adsorption On and Desorption From Swntssupporting
confidence: 87%
See 2 more Smart Citations
“…Optimization of the size and shape of the pores yields some improvement 5,6 but the hydrogen storage capacity of these materials remains too low for practical application. The main difficulty arises from the small adsortion energy [7][8][9][10] , below 100 meV, of hydrogen to the pore walls.…”
Section: Introductionmentioning
confidence: 99%